Kedudukan Suami Isteri dalam Rumah Tangga Berdasarkan Hukum Islam - Arnita Arnita (Kanun Jurnal Ilmu Hukum, 2011)
ABSTRACT: Such wording in an-Nisa (34) states that the position a husband in a family is higher than a wife due to the fact that a husband has an obligation and a bigger responsibility for a wife and children. Both f them are equal in rights and duties but the duties and responsibility to protect, keep from being sinful hat is forbidden by the religion and order the wife to act as demanded by the religion are under the responsibility and duty of a husband. A part from thot, the obligation to provide financial support is also part of the husband task. A wife who obeys to husband is going to be blessed as what she has done to her husban. The Position of Husband and Wife Based on Islamic Law